Zur Relevanz eines Prozessbereiches Interaktion und Exploration im Kontext informatischer Bildung im Primarbereich - Müller, Kathrin; Schulte, Carsten; Magenheim, Johannes (Informatik für alle, 18. GI-Fachtagung Informatik und Schule, (INFOS) 2019, 16.-18. September 2019, Dortmund)

Das RetiBNE Café - Schmidt, Ann-Katrin; Schulte, Carsten (Informatik für alle, 18. GI-Fachtagung Informatik und Schule, (INFOS) 2019, 16.-18. September 2019, Dortmund)

Shortest Paths in a Hybrid Network Model - Augustine, John; Hinnenthal, Kristian; Kuhn, Fabian; Scheideler, Christian; Schneider, Philipp (Proceedings of the Fourteenth Annual ACM-SIAM Symposium on Discrete Algorithms)

Critical Incidents for Technology Enhanced Learning in Vocational Education and Training - Wilke, Adrian; Magenheim, Johannes (IEEE Global Engineering Education Conference, EDUCON 2019, Dubai, United Arab Emirates, April 8-11, 2019)

Zieldimensionen für Multiplikatorinnen und Multiplikatoren früher MINT-Bildung - Köller, Olaf; Magenheim, Johannes; Molitor, Heike; Pfenning, Uwe; Ramseger, J{\; Steffensky, Mirjam; Wiesmüller, Christian; Winther, Esther; Wollring, Bernd

Time-dependent vibrational sum-frequency generation spectroscopy of the air-water interface - Ojha, Deepak; Kaliannan, Naveen Kumar; Kühne, Thomas D. (Communications Chemistry)

Accessing the Accuracy of Density Functional Theory through Structure and Dynamics of the Water–Air Interface - Ohto, Tatsuhiko; Dodia, Mayank; Xu, Jianhang; Imoto, Sho; Tang, Fujie; Zysk, Frederik; Kühne, Thomas D.; Shigeta, Yasuteru; Bonn, Mischa; Wu, Xifan; Nagata, Yuki (The Journal of Physical Chemistry Letters)

Unconventional phase III of high-pressure solid hydrogen - Azadi, Sam; Kühne, Thomas D. (Physical Review B)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas D.; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)

Deep reinforcement learning for wireless sensor scheduling in cyber–physical systems - Leong, Alex S.; Ramaswamy, Arunselvan; Quevedo, Daniel E.; Karl, Holger; Shi, Ling (Automatica)
In many cyber–physical systems, we encounter the problem of remote state estimation of geo- graphically distributed and remote physical processes. This paper studies the scheduling of sensor transmissions to estimate the states of multiple remote, dynamic processes. Information from the different sensors has to be transmitted to a central gateway over a wireless network for monitoring purposes, where typically fewer wireless channels are available than there are processes to be monitored. For effective estimation at the gateway, the sensors need to be scheduled appropriately, i.e., at each time instant one needs to decide which sensors have network access and which ones do not. To address this scheduling problem, we formulate an associated Markov decision process (MDP). This MDP is then solved using a Deep Q-Network, a recent deep reinforcement learning algorithm that is at once scalable and model-free. We compare our scheduling algorithm to popular scheduling algorithms such as round-robin and reduced-waiting-time, among others. Our algorithm is shown to significantly outperform these algorithms for many example scenario

Outsourced Decryption of Attribute-based Ciphertexts - Otte, Oliver

On the Security of the Rouselakis-Waters Ciphertext-Policy Attribute-Based Encryption Scheme in the Random Oracle Model - Wördenweber, Nico Christof

Improving CTC Using Stimulated Learning for Sequence Modeling - Heymann, Jahn; Khe Chai Sim, Bo Li (ICASSP 2019, Brighton, UK)
Connectionist temporal classification (CTC) is a sequence-level loss that has been successfully applied to train recurrent neural network (RNN) models for automatic speech recognition. However, one major weakness of CTC is the conditional independence assumption that makes it difficult for the model to learn label dependencies. In this paper, we propose stimulated CTC, which uses stimulated learning to help CTC models learn label dependencies implicitly by using an auxiliary RNN to generate the appropriate stimuli. This stimuli comes in the form of an additional stimulation loss term which encourages the model to learn said label dependencies. The auxiliary network is only used during training and the inference model has the same structure as a standard CTC model. The proposed stimulated CTC model achieves about 35% relative character error rate improvements on a synthetic gesture keyboard recognition task and over 30% relative word error rate improvements on the Librispeech automatic speech recognition tasks over a baseline model trained with CTC only.

An Investigation Into the Effectiveness of Enhancement in ASR Training and Test for Chime-5 Dinner Party Transcription - Zorila, Catalin; Boeddeker, Christoph; Doddipatla, Rama; Haeb-Umbach, Reinhold (ASRU 2019, Sentosa, Singapore)
Despite the strong modeling power of neural network acoustic models, speech enhancement has been shown to deliver additional word error rate improvements if multi-channel data is available. However, there has been a longstanding debate whether enhancement should also be carried out on the ASR training data. In an extensive experimental evaluation on the acoustically very challenging CHiME-5 dinner party data we show that: (i) cleaning up the training data can lead to substantial error rate reductions, and (ii) enhancement in training is advisable as long as enhancement in test is at least as strong as in training. This approach stands in contrast and delivers larger gains than the common strategy reported in the literature to augment the training database with additional artificially degraded speech. Together with an acoustic model topology consisting of initial CNN layers followed by factorized TDNN layers we achieve with 41.6% and 43.2% WER on the DEV and EVAL test sets, respectively, a new single-system state-of-the-art result on the CHiME-5 data. This is a 8% relative improvement compared to the best word error rate published so far for a speech recognizer without system combination.

Experimentelle Untersuchung des SEM-Algorithmus - Leutnant, Matthias

Android App Merging for Benchmark Speed-Up and Analysis Lift-Up - Pauck, Felix; Zhang, Shikun (2019 34th IEEE/ACM International Conference on Automated Software Engineering Workshop (ASEW))
In the field of software analysis a trade-off between scalability and accuracy always exists. In this respect, Android app analysis is no exception, in particular, analyzing large or many apps can be challenging. Dealing with many small apps is a typical challenge when facing micro-benchmarks such as DROIDBENCH or ICC-BENCH. These particular benchmarks are not only used for the evaluation of novel tools but also in continuous integration pipelines of existing mature tools to maintain and guarantee a certain quality-level. Considering this latter usage it becomes very important to be able to achieve benchmark results as fast as possible. Hence, benchmarks have to be optimized for this purpose. One approach to do so is app merging. We implemented the Android Merge Tool (AMT) following this approach and show that its novel aspects can be used to produce scaled up and accurate benchmarks. For such benchmarks Android app analysis tools do not suffer from the scalability-accuracy trade-off anymore. We show this throughout detailed experiments on DROIDBENCH employing three different analysis tools (AMANDROID, ICCTA, FLOWDROID). Benchmark execution times are largely reduced without losing benchmark accuracy. Moreover, we argue why AMT is an advantageous successor of the state-of-the-art app merging tool (APKCOMBINER) in analysis lift-up scenarios.
Keywords: Program Analysis; Android App Analysis; Taint Analysis; App Merging; Benchmark

Predicting plasticity and fracture of severe pre-strained EN AW-5182 by Yld2000 yield locus and Hosford-Coulomb fracture model in sheet forming applications - Camberg, Alan Adam; Tröster, Thomas; Bohner, F.; Tölle, J. (IOP Conference Series: Materials Science and Engineering)

Incremental learning with Support Vector Machine on embedded platforms - Kumar Jeyakumar, Shankar

"Johnny, you are fired!" -- Spoofing OpenPGP and S/MIME Signatures in Emails - Müller, Jens; Brinkmann, Marcus; Poddebniak, Damian; Böck, Hanno; Schinzel, Sebastian; Somorovsky, Juraj; Schwenk, Jörg (28th USENIX Security Symposium (USENIX Security 19))

Scalable Scanning and Automatic Classification of TLS Padding Oracle Vulnerabilities - Merget, Robert; Somorovsky, Juraj; Aviram, Nimrod; Young, Craig; Fliegenschmidt, Janis; Schwenk, Jörg; Shavitt, Yuval (28th USENIX Security Symposium (USENIX Security 19))

Security Analysis of XAdES Validation in the CEF Digital Signature Services (DSS) - Engelbertz, Nils; Mladenov, Vladislav; Somorovsky, Juraj; Herring, David; Erinola, Nurullah; Schwenk, Jörg (Open Identity Summit 2019)

A Bitstream-Level Proof-Carrying Hardware Technique for Information Flow Tracking - Keerthipati, Monica
Secure hardware design is the most important aspect to be considered in addition to functional correctness. Achieving hardware security in today’s globalized Integrated Cir- cuit(IC) supply chain is a challenging task. One solution that is widely considered to help achieve secure hardware designs is Information Flow Tracking(IFT). It provides an ap- proach to verify that the systems adhere to security properties either by static verification during design phase or dynamic checking during runtime. Proof-Carrying Hardware(PCH) is an approach to verify a functional design prior to using it in hardware. It is a two-party verification approach, where the target party, the consumer requests new functionalities with pre-defined properties to the producer. In response, the producer designs the IP (Intellectual Property) cores with the requested functionalities that adhere to the consumer-defined properties. The producer provides the IP cores and a proof certificate combined into a proof-carrying bitstream to the consumer to verify it. If the verification is successful, the consumer can use the IP cores in his hardware. In essence, the consumer can only run verified IP cores. Correctly applied, PCH techniques can help consumers to defend against many unintentional modifications and malicious alterations of the modules they receive. There are numerous published examples of how to use PCH to detect any change in the functionality of a circuit, i.e., pairing a PCH approach with functional equivalence checking for combinational or sequential circuits. For non-functional properties, since opening new covert channels to leak secret information from secure circuits is a viable attack vector for hardware trojans, i.e., intentionally added malicious circuitry, IFT technique is employed to make sure that secret/untrusted information never reaches any unclassified/trusted outputs. This master thesis aims to explore the possibility of adapting Information Flow Tracking into a Proof-Carrying Hardware scenario. It aims to create a method that combines Infor- mation Flow Tracking(IFT) with a PCH approach at bitstream level enabling consumers to validate the trustworthiness of a module’s information flow without the computational costs of a complete flow analysis.

Ranking on Very Large Knowledge Graphs - Desouki, Abdelmoneim Amer; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 30th ACM Conference on Hypertext and Social Media - HT '19)
Ranking plays a central role in a large number of applications driven by RDF knowledge graphs. Over the last years, many popular RDF knowledge graphs have grown so large that rankings for the facts they contain cannot be computed directly using the currently common 64-bit platforms. In this paper, we tackle two problems: Computing ranks on such large knowledge bases efficiently and incrementally. First, we present D-HARE, a distributed approach for computing ranks on very large knowledge graphs. D-HARE assumes the random surfer model and relies on data partitioning to compute matrix multiplications and transpositions on disk for matrices of arbitrary size. Moreover, the data partitioning underlying D-HARE allows the execution of most of its steps in parallel. As very large knowledge graphs are often updated periodically, we tackle the incremental computation of ranks on large knowledge bases as a second problem. We address this problem by presenting I-HARE, an approximation technique for calculating the overall ranking scores of a knowledge without the need to recalculate the ranking from scratch at each new revision. We evaluate our approaches by calculating ranks on the 3 × 10^9 and 2.4 × 10^9 triples from Wikidata resp. LinkedGeoData. Our evaluation demonstrates that D-HARE is the first holistic approach for computing ranks on very large RDF knowledge graphs. In addition, our incremental approach achieves a root mean squared error of less than 10E−7 in the best case. Both D-HARE and I-HARE are open-source and are available at: https://github.com/dice-group/incrementalHARE.
Keywords: Knowledge Graphs; Ranking; RDF

Debiasing Vandalism Detection Models at Wikidata (Extended Abstract) - Heindorf, Stefan; Scholten, Yan; Engels, Gregor; Potthast, Martin (INFORMATIK)

Advances and novel applications of mobile wireless networking - Sommer, Christoph; Basagni, Stefano (Ad Hoc Networks)

Modeling Cycling Behavior to Improve Bicyclists' Safety at Intersections - A Networking Perspective - Heinovski, Julian; Stratmann, Lukas; Buse, Dominik S.; Klingler, Florian; Franke, Mario; Oczko, Marie-Christin H.; Sommer, Christoph; Scharlau, Ingrid; Dressler, Falko (2019 IEEE 20th International Symposium on "A World of Wireless, Mobile and Multimedia Networks" (WoWMoM))

Aufführungs- und zensurbedingte Veränderungen im Wiener Manuskript der Freischütz-Erstaufführung 1821 in Wien - Seipelt, Agnes Regina (Weberiana)
Keywords: Weber; Wien; Zensur

A Study on Online Source Extraction in the Presence of Changing Speaker Positions - Heitkaemper, Jens; Feher, Thomas; Freitag, Michael; Haeb-Umbach, Reinhold (International Conference on Statistical Language and Speech Processing 2019, Ljubljana, Slovenia)
Multi-talker speech and moving speakers still pose a significant challenge to automatic speech recognition systems. Assuming an enrollment utterance of the target speakeris available, the so-called SpeakerBeam concept has been recently proposed to extract the target speaker from a speech mixture. If multi-channel input is available, spatial properties of the speaker can be exploited to support the source extraction. In this contribution we investigate different approaches to exploit such spatial information. In particular, we are interested in the question, how useful this information is if the target speaker changes his/her position. To this end, we present a SpeakerBeam-based source extraction network that is adapted to work on moving speakers by recursively updating the beamformer coefficients. Experimental results are presented on two data sets, one with articially created room impulse responses, and one with real room impulse responses and noise recorded in a conference room. Interestingly, spatial features turn out to be advantageous even if the speaker position changes.

Multi-Channel Block-Online Source Extraction based on Utterance Adaptation - Martin-Donas, Juan M.; Heitkaemper, Jens; Haeb-Umbach, Reinhold; Gomez, Angel M.; Peinado, Antonio M. (INTERSPEECH 2019, Graz, Austria)
This paper deals with multi-channel speech recognition in scenarios with multiple speakers. Recently, the spectral characteristics of a target speaker, extracted from an adaptation utterance, have been used to guide a neural network mask estimator to focus on that speaker. In this work we present two variants of speakeraware neural networks, which exploit both spectral and spatial information to allow better discrimination between target and interfering speakers. Thus, we introduce either a spatial preprocessing prior to the mask estimation or a spatial plus spectral speaker characterization block whose output is directly fed into the neural mask estimator. The target speaker’s spectral and spatial signature is extracted from an adaptation utterance recorded at the beginning of a session. We further adapt the architecture for low-latency processing by means of block-online beamforming that recursively updates the signal statistics. Experimental results show that the additional spatial information clearly improves source extraction, in particular in the same-gender case, and that our proposal achieves state-of-the-art performance in terms of distortion reduction and recognition accuracy.

Guided Source Separation Meets a Strong ASR Backend: Hitachi/Paderborn University Joint Investigation for Dinner Party ASR - Kanda, Naoyuki; Boeddeker, Christoph; Heitkaemper, Jens; Fujita, Yusuke; Horiguchi, Shota; Haeb-Umbach, Reinhold (INTERSPEECH 2019, Graz, Austria)
In this paper, we present Hitachi and Paderborn University’s joint effort for automatic speech recognition (ASR) in a dinner party scenario. The main challenges of ASR systems for dinner party recordings obtained by multiple microphone arrays are (1) heavy speech overlaps, (2) severe noise and reverberation, (3) very natural onversational content, and possibly (4) insufficient training data. As an example of a dinner party scenario, we have chosen the data presented during the CHiME-5 speech recognition challenge, where the baseline ASR had a 73.3% word error rate (WER), and even the best performing system at the CHiME-5 challenge had a 46.1% WER. We extensively investigated a combination of the guided source separation-based speech enhancement technique and an already proposed strong ASR backend and found that a tight combination of these techniques provided substantial accuracy improvements. Our final system achieved WERs of 39.94% and 41.64% for the development and evaluation data, respectively, both of which are the best published results for the dataset. We also investigated with additional training data on the official small data in the CHiME-5 corpus to assess the intrinsic difficulty of this ASR task.

Digitale Musikanalyse auf Grundlage von MEI-codierten Daten - Seipelt, Agnes Regina; Klugseder, Robert (Musik im Zusammenhang: Festschrift Peter Revers zum 65. Geburtstag)

The 31st ACM Symposium on Parallelism in Algorithms and Architectures, SPAA 2019, Phoenix, AZ, USA, June 22-24, 2019

Self-Stabilizing Metric Graphs - Gmyr, Robert; Lefevre, Jonas; Scheideler, Christian (Theory Comput. Syst.)

FPGA Acceleration of String Search Techniques in Huge Data Sets - Sabu, Nithin S.

Using Just-in-Time Code Generation to Transparently Accelerate Applications in Heterogeneous Systems - Vaz, Gavin Francis

On Scheduling with Setup Times - Mäcker, Alexander

Atomization of Fluids with Ultrasound - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter; Sextro, Walter (Conference Proceedings - The 4th Conference on MicroFluidic Handling Systems (MFHS2019))
In a variety of industrial applications, liquids are atomized to produce aerosols for further processing. Example applications are the coating of surfaces with paints, the application of ultra-thin adhesive layers and the atomization of fuels for the production of combustible dispersions. In this publication different atomizing principles (standing-wave, capillary-wave, vibrating-mesh) are examined and discussed. Using an optimized standing-wave system, tough liquids with viscosities of up to about 100 Pas could be successfully atomized.
Keywords: atomization; ultrasound; standing-wave; capillarywave; vibrating-mesh

Simultaneous Spectral and Spatial Modulation for Color Printing and Holography Using All-dielectric Metasurfaces - Wei, Qunshuo; Sain, Basudeb; Wang, Yongtian; Reineke, Bernhard; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (Nano Letters)

Exploiting Counterfactuals for Scalable Stochastic Optimization - Kuhlemann, Stefan; Sellmann, Meinolf; Tierney, Kevin (Lecture Notes in Computer Science)

ModGuard: Identifying Integrity &Confidentiality Violations in Java Modules - Dann, Andreas; Hermann, Ben; Bodden, Eric (IEEE Transactions on Software Engineering)

SootDiff: bytecode comparison across different Java compilers - Dann, Andreas; Hermann, Ben; Bodden, Eric (Proceedings of the 8th ACM SIGPLAN International Workshop on State Of the Art in Program Analysis - SOAP 2019)

Can an Online Service Predict Gender? On the State-of-the-Art in Gender Identification from Texts - Kruger, Stefan; Hermann, Ben (2019 IEEE/ACM 2nd International Workshop on Gender Equality in Software Engineering (GE))

Analyse der Veränderung der zwischenstaatlichen Gewinnaufteilung bei Einführung einer standardisierten Gewinnverteilungsmethode am Beispiel des Einsatzes von 3D-Druckern - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren

Steuerkomplexität im Vergleich zwischen Deutschland und Österreich - Eine Analyse des Status quo - Hoppe, Thomas; Rechbauer, Martina; Sturm, Susann (Steuer und Wirtschaft)
Die Komplexität von Steuersystemen gewinnt in der Debatte um den internationalen Steuerwettbewerb zunehmend an Bedeutung. Im vorliegenden Beitrag erfolgt, basierend auf den Befragungsdaten, die dem Tax Complexity Index von Hoppe et al. (2019) zugrunde liegen, eine umfassende Gegenüberstellung der Komplexität der Steuersysteme von Deutschland und Österreich unter Berücksichtigung der Mittelwerte aller vom Index abgedeckten Länder. Die Steuergesetze weisen sowohl in Deutschland als auch in Österreich einen verhältnismäßig hohen Grad an Komplexität auf. Bei den steuerlichen Rahmenbedingungen fällt der Grad an Komplexität in beiden Ländern dagegen niedrig aus, wobei Österreich im Durchschnitt weniger komplex ist als Deutschland.

Violations of Dominance in Decision-Making - Kourouxous, Thomas; Bauer, Thomas (Business Research)
A key premise underlying most of the economic literature is that rational decision-makers will choose dominant strategies over dominated alternatives. However, prior literature in various disciplines including business, psychology, and economics document a series of phenomena associated with violations of the dominance principle in decision-making. In this comprehensive review, we discuss conditions under which people violate the dominance principle in decision-making. When presenting violations of dominance in empirical and experimental studies, we differentiate between absolute, statewise, and stochastic (first- and second-order) violations of dominance. Furthermore, we categorize the literature by the leading causes for dominance violations: framing, reference points, certainty effects, bounded rationality, and emotional responses.

Using Impact Evaluation to Examine Domestic and International Cooperative Compliance Programs - Majdanska, Alicja; Wu, Yuchen (Tax Notes International)

Coupled microstrip-cavities under oblique incidence of semi-guided waves: a lossless integrated optical add-drop filter - Ebers, Lena; Hammer, Manfred; Berkemeier, Manuel B.; Menzel, Alexander; Förstner, Jens (OSA Continuum)
We investigate optical microresonators consisting of either one or two coupled rectangular strips between upper and lower slab waveguides. The cavities are evanescently excited under oblique angles by thin-film guided, in-plane unguided waves supported by one of the slab waveguides. Beyond a specific incidence angle, losses are fully suppressed. The interaction between the guided mode of the cavity-strip and the incoming slab modes leads to resonant behavior for specific incidence angles and gaps. For a single cavity, at resonance, the input power is equally split among each of the four output ports, while for two cavities an add-drop filter can be realized that, at resonance, routes the incoming power completely to the forward drop waveguide via the cavity. For both applications, the strength of the interaction is controlled by the gaps between cavities and waveguides.
Keywords: tet_topic_waveguides

Fuzzy Sets in Data Analysis: From Statistical Foundations to Machine Learning - Couso, Ines; Borgelt, Christian; Hüllermeier, Eyke; Kruse, Rudolf (IEEE Computational Intelligence Magazine)

Multi-target prediction: a unifying view on problems and methods - Waegeman, Willem; Dembczynski, Krzysztof; Hüllermeier, Eyke (Data Mining and Knowledge Discovery)
Many problem settings in machine learning are concerned with the simultaneous prediction of multiple target variables of diverse type. Amongst others, such problem settings arise in multivariate regression, multi-label classification, multi-task learning, dyadic prediction, zero-shot learning, network inference, and matrix completion. These subfields of machine learning are typically studied in isolation, without highlighting or exploring important relationships. In this paper, we present a unifying view on what we call multi-target prediction (MTP) problems and methods. First, we formally discuss commonalities and differences between existing MTP problems. To this end, we introduce a general framework that covers the above subfields as special cases. As a second contribution, we provide a structured overview of MTP methods. This is accomplished by identifying a number of key properties, which distinguish such methods and determine their suitability for different types of problems. Finally, we also discuss a few challenges for future research.

Set-Valued Prediction in Multi-Class Classification - Mortier, Thomas; Wydmuch, Marek; Dembczynski, Krzysztof; Hüllermeier, Eyke; Waegeman, Willem (Proceedings of the 31st Benelux Conference on Artificial Intelligence {(BNAIC} 2019) and the 28th Belgian Dutch Conference on Machine Learning (Benelearn 2019), Brussels, Belgium, November 6-8, 2019)

Feature Selection for Analogy-Based Learning to Rank - Ahmadi Fahandar, Mohsen; Hüllermeier, Eyke (Discovery Science)

Analogy-Based Preference Learning with Kernels - Ahmadi Fahandar, Mohsen; Hüllermeier, Eyke (KI 2019: Advances in Artificial Intelligence)

Epistemic Uncertainty Sampling - Nguyen, Vu-Linh; Destercke, Sébastien; Hüllermeier, Eyke (Discovery Science)

Learning to Aggregate: Tackling the Aggregation/Disaggregation Problem for OWA - Melnikov, Vitaly; Hüllermeier, Eyke (Proceedings ACML, Asian Conference on Machine Learning (Proceedings of Machine Learning Research, 101))

Influence of Cruise Control on Driver Guidance - a Comparison between System Generations and Countries - Epple, Nico; Dari, Simone; Drees, Ludwig; Protschky, Valentin; Riener, Andreas (2019 IEEE Intelligent Vehicles Symposium (IV))

Algorithm Selection as Recommendation: From Collaborative Filtering to Dyad Ranking - Tornede, Alexander; Wever, Marcel Dominik; Hüllermeier, Eyke (Proceedings - 29. Workshop Computational Intelligence, Dortmund, 28. - 29. November 2019)

A Reduction of Label Ranking to Multiclass Classification - Brinker, Klaus; Hüllermeier, Eyke (Proceedings ECML/PKDD, European Conference on Machine Learning and Knowledge Discovery in Databases)

Learning from Imprecise Data: Adjustments of Optimistic and Pessimistic Variants - Hüllermeier, Eyke; Couso, Ines; Diestercke, Sebastian (Proceedings SUM 2019, International Conference on Scalable Uncertainty Management)

Mining Rank Data - Henzgen, Sascha; Hüllermeier, Eyke (ACM Transactions on Knowledge Discovery from Data)

Intrinsically lubricated tool inserts for deep drawing applications generated by selective laser melting - Bader, Fabian; Hengsbach, Florian; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)
Abstract. Within the scope of this study, an intrinsically lubricated deep drawing die fabricated via laser beam melting (LBM) is investigated. In contrast to the common objective of generating highly dense LBM components, this work endeavors to achieve intended micro-scale porosity. By utilizing permeable structures, in-process closed-loop control of lubrication during the forming operations is feasible. Based on a modified AM scan strategy, the required filigree, porous structures can be generated. Thus, in the present work three permeable specimens are additively generated from the maraging steel 1.2709. The cylindrical specimens are then analyzed via light microscopy (LM), microcomputer tomography (microCT), and with regard to the oil throughput rate. Subsequently, an intrinsically lubricated, AM deep drawing tool die is manufactured and experimentally tested. The findings reveal interesting results for deep drawn specimens with AM deep drawing dies.

Al2O3/ZrO2-8Y2O3 and (Cr,Ti)AlSiN tool coatings to influence the temperature and surface quality in friction-spinning processes - Tillmann, Wolfgang; Fehr, Alexander; Stangier, Dominic; Dildrop, Markus; Homberg, Werner; Lossen, Benjamin; Hijazi, Dina (Production Engineering)
Friction-spinning is an incremental forming process, which is accompanied by complex thermal and mechanical loads in the tool and the formed part. To influence the process temperature, two main process parameters, i.e. the rotation speed and the feed rate, can be adapted. With the objective to improve the tool performance and the quality of the workpiece, this study focuses on a coating concept for friction-spinning tools made of high speed steel (HS6 5 2C, 1.3343). On the one hand, atmospheric plasma sprayed (APS) Al2O3 and ZrO2-8Y2O3 coatings serve as a thermal insulator, and, on the other hand, physically vapor deposited (PVD) TiAlSi7.9N and CrAlSi7.5N films are applied to increase the hardness and wear resistance of the tools. In addition, duplex coatings, combining the APS and PVD technique, are synthesized to influence both the heat transfer and the tribological properties of friction-spinning tools. Subsequently, all coated tools are tested in a friction-spinning process to form flanges made of AW-6060 (AlMgSi 3.3206) tube materials. The tool temperatures are determined in-situ to investigate the impact of the tool coating on the process temperature. Compared to an uncoated tool, the alumina and zirconia coatings contribute to a reduction of the tool temperature by up to half, while the PVD films increase the hardness of the tool by 20 GPa. Furthermore, it is shown that the surface quality of thermally sprayed (TS) or PVD coated tools is directly related to the surface roughness of the resulting workpiece.

Ein Beitrag zur kombinierten (quasi-)statischen und dynamischen Umformung von blechförmigen Halbzeugen - Djakow, Eugen
Working-media-based forming processes (WMBF) represent a great potential regarding the production of complex sheet-metal lightweight components with excellent surface quality, shape accuracy and dimensional stability. The working-media-based forming processes characterize the sheet-metal forming process, where the sheet metal blank is formed during the forming process by means of a (quasi-)static or dynamic working media pressure into a contouring forming tool. Although the WMBF offers improved utilization of the formability of the used materials compared to conventional sheet metal forming processes, there are limits in the production of complex deeper or sharp edged components with (quasi-)static and dynamic WMBF processes, which can not be overcome by using these methods alone. In order to overcome this, multi-level WMBF process sequences for components with spherical and stepped geometries are developed in this work. Here the developed strategies combine the advantages of (quasi-)static and dynamic WMBF processes. Furthermore, based on analytical, experimental and numerical investigations, innovative process management strategies were derived, which completely compensate the local wall thickness changes, make better use of existing material resources and thus enable the safe production of mentioned geometries.
Keywords: High Speed Forming

High-Speed Incremental Forming – New Technologies For Flexible Production Of Sheet Metal Parts - Linnemann, M.; Psyk, V.; Djakow, Eugen; Springer, R.; Homberg, W.; Landgrebe, D. (Procedia Manufacturing)

Heat transfer enhancement in pillow-plate heat exchangers with dimpled surfaces: A numerical study - Piper, M.; Zibart, A.; Djakow, Eugen; Springer, R.; Homberg, W.; Kenig, E.Y. (Applied Thermal Engineering)

How Good Is Good Enough? Establishing Quality Thresholds for the Automatic Text Analysis of Retro-Digitized Comics - Hartel, Rita; Dunst, Alexander (International Conference on Multimedia Modeling, MMM)

Tomographische Untersuchung der Fluiddynamik viskoser Systeme in Packungskolonnen - Bolenz, Lukas; Fischer, Florian; Toye, Dominique; Kenig, Eugeny (Chemie Ingenieur Technik)

Liquid Flow Morphology of Viscous Systems in Structured Packings: Investigations by X-ray Tomography - Bolenz, Lukas; Toye, Dominique; Kenig, Eugeny (Chemical Engineering Transactions)

Tomographische Untersuchung der Fluiddynamik viskoser Systeme in Packungskolonnen - Bolenz, Lukas; Toye, Dominique; Kenig, Eugeny

Experimental and theoretical investigation of fluid dynamics in structured packings - Bolenz, Lukas; Toye, Dominique; Kenig, Eugeny

Liquid Flow Morphology of Viscous Systems in Structured Packings: Investigations by X-ray Tomography - Bolenz, Lukas; Toye, Dominique; Kenig, Eugeny

Modellierung des Stofftransports in Füllkörperkolonnen mit dem Ansatz der hydrodynamischen Analogien - Salten, Alexander Heinrich Johannes; Maćkowiak, Jan F.; Maćkowiak, Jerzy; Kenig, Eugeny

A hydrodynamic analogy based modelling approach for zero-gravity distillation with metal foams - Rieks, Sebastian; Wende, Marc; Preußer, Niklas; Gambaryan-Roisman, Tatiana; Kenig, Eugeny (Chemical Engineering Research and Design)

Modellierungsansatz zur Simulation von Gravidestillation mit Metallschäumen - Wende, Marc; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppe Wärme- und Stoffübertragung)

Simulation von Gravidestillationsprozessen mit Metallschäumen - Wende, Marc; Staggenborg, Christoph; Kenig, Eugeny (Workshop Wärmeübertragung mit Phasenwechsel in fluiden Systemen: Ein Update)

A sensitivity-based optimisation procedure for the characterisation of piezoelectric discs - Feldmann, Nadine; Jurgelucks, Benjamin; Claes, Leander; Henning, Bernd (2019 International Congress on Ultrasonics)

Fachbezogene Reflexion in der beruflichen Lehrer*innenbildung - Jenert, Tobias; Brahm, Taiga; Naeve-Stoß, Nicole (bwpat)

Untangling Faculty Misinformation From an Educational Perspective: Rejoinder to ''The Menace of Misinformation: Faculty Misstatements in Management Education and Their Consequences'' - Jenert, Tobias; Brahm , Taiga (Journal of Management Education)

Theorie und Praxis der Hochschulbildungsforschung

Multimodale Stilometrie: Herausforderungen und Potenzial kombinatorischer Bild- und Textanalysen am Beispiel Comics - Dunst, Alexander; Hartel, Rita (DHd Konferenz 2019, multimedial und multimodal)

Quantifying Complexity in Multimodal Media: AlanMoore and the “Density” of the Graphic Novel - Dunst, Alexander; Hartel, Rita (Digital Humanities, DH 2019)

The Decomposability of the Nash Bargaining Solution in Labor Markets - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya
In this paper, we analyze the two-dimensional Nash bargaining solution (NBS) deploying a standard labor market negotiations model (see McDonald and Solow, 1981; Creedy and McDonald, 1991). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems such that the (Cartesian) product of the solutions of these problems replicates the solution of the two-dimensional problem, if the NBS is applied. However, this decomposition fails for any solution concept that does not satisfy the axiom of Independence of Irrelevant Alternatives (IIA axiom). Our decomposition result has significant implications for actual negotiations, as it allows for the decomposition of a multi-issue bargaining problem into a set of simpler problems, in particular a set of single-issue bargaining problems. In this way, the decomposition may help facilitate negotiations in labor markets and also in other environments.
Keywords: Labor market negotiations; Efficient bargains; Nash bargaining solution; Sequential bargaining; Restricted bargaining games

Duality for General TU-games Redefined - Aslan, Fatma; Duman, Papatya; Trockel, Walter
We criticize some conceptual weaknesses in the recent literature on coalitional TUgames and propose, based on our critics, a new definition of dual TU-games that coincides with the one in the literature on the class of super-additive games. We justify our new definition in four alternative ways: 1. Via an adequate definition of ecient payo vectors. 2. Via a modification of the Bondareva-Shapley duality. 3. Via an explicit consideration of \coalition building". 4. Via associating general TU-games to coalition-production economies. Rather than imputations, we base our analysis on a modification of aspirations.
Keywords: TU-games; duality; core; c-Core; cohesive games; complete game efficiency

Proceedings of the 6th Workshop on Argument Mining

Messung hochfrequenter In-Plane-Schwingungen mittels Laservibrometrie in räumlich eingeschränkten Umgebungen - Hagedorn, Oliver Ernst Caspar; Pielsticker, Daniel; Hemsel, Tobias; Sextro, Walter (2. VDI-Fachtagung Schwingungen 2019)

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Analysis of Lamb wave mode repulsion and its implications to the characterisation of adhesive bonding strength - Lugovtsova, Yevgeniya; Johannesmann, Sarah; Henning, Bernd; Prager, Jens (2019 International Congress on Ultrasonics)

Projektmanagement und Vorgehensmodelle 2019. Neue Vorgehensmodelle in Projekten – Führung, Kulturen und Infrastrukturen im Wandel.

The Collaboration of Human Resource Management and Line Management–An International Comparison - Szierbowski-Seibel, Klaas; Wach, Bernhard A.; Kabst, Rüdiger (Organization Management Journal)

Impact of national culture on organizations’ use of selection practices - Prince, Nicholas Ryan; Kabst, Rüdiger (Employee Relations: The International Journal)
Purpose The purpose of this paper is to investigate the impact of national culture on organizations’ use of selection practices, specifically to investigate the impact of in-group collectivism, uncertainty avoidance and power distance on interview panels, one-on-one interviews, applications forms, references, ability, technical and psychometric tests. Design/methodology/approach This study uses survey data from the 2008–2010 CRANET database. It uses OLS regression analysis to test the impact of national culture on organizations’ use of selection practices. Findings In-group collectivism increases the use of panel interviews and technical tests, and decreases the use of one-on-one interviews and application forms. Uncertainty avoidance increases the use of panel interviews and technical tests, and a decrease in one-on-one interviews, applications ability, and psychometric tests. Power distance leads to an increase in one-on-one interviews, applications and ability tests, and a decrease in panel interviews, psychometric tests and references. Originality/value This paper investigates the use of the impact of national culture on selection practices. Specifically, it looks at the use of a large number of selection practices panel interviews, one-on-one interviews, applications and references, and several different tests, ability, technical and psychometric.

Multithreaded Software/Hardware Programming with ReconOS/freeRTOS on a Recon􏰃gurable System-on-Chip - Mehta, Jinay

Fracture prediction of additively manufactured AlSi10Mg materials - Akbulut Irmak, Emine Fulya; Tröster, Thomas (Procedia Structural Integrity)

Modeling the Energy Absorption Characteristics of Wood Crash Elements - Akbulut Irmak, Emine Fulya; Hanses, Julius; Schweizer, Swetlana; Tröster, Thomas

Einsatz neuartiger Stähle und Generierung gradierter Leichtbaustrukturen im Presshärteprozess - Marten, Thorsten; Tröster, Thomas

Press Hardening Integrated Structuring for Hybrid Components - Triebus, Marcel; Bienia, S.; Marten, Thorsten; Tröster, Thomas; Dröder, K.

Evolutionary algorithm for the design of passive electric matching networks for ultrasonic transducers - Hetkämper, Tim; Claes, Leander; Henning, Bernd (2019 International Congress on Ultrasonics)

Scalability of parametric down-conversion for generating higher-order Fock states - Tiedau, Johannes; Bartley, Tim; Harder, Georg; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review A)

Verifying Correctness of Persistent Concurrent Data Structures - Derrick, John; Doherty, Simon; Dongol, Brijesh; Schellhorn, Gerhard; Wehrheim, Heike (Formal Methods - The Next 30 Years - Third World Congress, FM 2019, Porto, Portugal, October 7-11, 2019, Proceedings)

Editorial - Russo, Alessandra; Schürr, Andy; Wehrheim, Heike (Formal Asp. Comput.)

Editorial - Fränzle, Martin; Kapur, Deepak; Wehrheim, Heike; Zhan, Naijun (Formal Asp. Comput.)